Branding strategy for entry to new markets. An institutional and cultural approach: bimbo group case - Vargas Hernández, José; Adame Rodríguez, Laura; Flores Murguía, Raquel de Guadalupe (mktDESCUBRE; Vol 1 No 12 (2018): Twelfth Edition - (July - December), 2018)
The objective of this research is to determine if branding strategies have allowed Grupo Bimbo to participate in new markets, through an analysis from an institutional and cultural approach, to determine the branding strategy in the case study of Grupo Bimbo and its participation in three Latin American countries (Argentina, Brazil and Peru). It is based on a qualitative method, with a descriptive and explanatory study, through documentary research and the use of the interview as an instrument for data collection, and given the problems and strategies of the case under study, the result is the branding used for the 3 markets mentioned above.